POLA PERESEPAN OBAT ANTIDIABETIK PADA PASIEN DIABETES MELLITUS TIPE II DI PUSKESMAS PANDAK 1 BANTUL - Rissa, Mexsi Mutia; Amallia Rani Wijayanti (Jurnal Insan Farmasi Indonesia, 2024)
Diabetes mellitus in Indonesia is in the top five countries with the most DM sufferers, namely 19.5 million people and this number will increase to 28.6 million people in 2045. If diabetes is not treated properly loss of vision, kidney failure, nerves, limb amputation, and can cause premature death. This study aims to determine the pattern of prescribing for type II diabetes mellitus medication at the Pandak I Bantul Community Health Center for the period 2022. The research methodology used is descriptive observational with retrospective collection of medical record data with a sample of 90 medical records. The results of research on the prescribing pattern for type II diabetes mellitus drugs at the Pandak I Community Health Center consisted of the use of single diabetes mellitus drugs, namely 73.33% of metformin 500 mg, 24.45% of glimepirid 2 mg and 2.22% of glibenclamide 5 mg. The percentages are based on drug class, namely the biguanide group 73.33% and the sulfonylurea group 26.67%. So the pattern of prescribing medication for type II diabetes mellitus at the Pandak I Community Health Center with the single treatment mostly using metformin 500 mg with the biguanide group is 73.33%.